Next-generation sequencing reveals deep intronic cryptic ABCC8 and HADH splicing founder mutations causing hyperinsulinism by pseudoexon activation. - O'SULLIVAN, MAUREEN (My University, 2013)
Next-generation sequencing (NGS) enables analysis of the human genome on a scale previously unachievable by Sanger sequencing. Exome sequencing of the coding regions and conserved splice sites has been very successful in the identification of disease-causing mutations, and targeting of these regions has extended clinical diagnostic testing from analysis of fewer than ten genes per phenotype to more than 100. Noncoding mutations have been less extensively studied despite evidence from mRNA analysis for the existence of deep intronic mutations in >20 genes. We investigated individuals with hyperinsulinaemic hypoglycaemia and biochemical or genetic evidence to suggest noncoding mutations by using NGS to analyze the entire genomic regions of ABCC8 (117 kb) and HADH (94 kb) from overlapping ~10 kb PCR amplicons. Two deep intronic mutations, c.1333-1013A>G in ABCC8 and c.636+471G>T HADH, were identified. Both are predicted to create a cryptic splice donor site and an out-of-frame pseudoexon. Sequence analysis of mRNA from affected individuals? fibroblasts or lymphoblastoid cells confirmed mutant transcripts with pseudoexon inclusion and premature termination codons. Testing of additional individuals showed that these are founder mutations in the Irish and Turkish populations, accounting for 14% of focal hyperinsulinism cases and 32% of subjects with HADH mutations in our cohort. The identification of deep intronic mutations has previously focused on the detection of aberrant mRNA transcripts in a subset of disorders for which RNA is readily obtained from the target tissue or ectopically expressed at sufficient levels. Our approach of using NGS to analyze the entire genomic DNA sequence is applicable to any disease.
PUBLISHED
Keywords: Hyperinsulinism